2013
DOI: 10.1111/1471-0528.12217
|View full text |Cite
|
Sign up to set email alerts
|

Salivary progesterone as a biochemical marker to predict early preterm birth in asymptomatic high‐risk women

Abstract: Objective To evaluate salivary progesterone as a predictor of early preterm birth (PTB) and compare it with transvaginal sonographic (TVS) cervical length in asymptomatic high-risk women.Design Prospective study.Setting Departments of Obstetrics and Gynaecology and Biochemistry at UCMS & GTBH, Delhi, India.Sample Ninety pregnant women.Methods The progesterone concentration in saliva of asymptomatic pregnant women at high risk for preterm delivery was estimated by immunoassay, and cervical length was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Whereas some later studies have also found lower plasma progesterone concentrations in the third trimester in preterm vs term labor in women with a previous preterm birth, 4 others have found no difference in maternal progesterone concentrations in either serum or amniotic fluid. 14 A more consistent finding has been lower progesterone : estradiol ratios in women in labor compared with women not in labor both preterm and term. 14 A more consistent finding has been lower progesterone : estradiol ratios in women in labor compared with women not in labor both preterm and term.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas some later studies have also found lower plasma progesterone concentrations in the third trimester in preterm vs term labor in women with a previous preterm birth, 4 others have found no difference in maternal progesterone concentrations in either serum or amniotic fluid. 14 A more consistent finding has been lower progesterone : estradiol ratios in women in labor compared with women not in labor both preterm and term. 14 A more consistent finding has been lower progesterone : estradiol ratios in women in labor compared with women not in labor both preterm and term.…”
Section: Introductionmentioning
confidence: 93%
“…[4][5][6][7][8][9][10][11][12] Recent studies have found low saliva progesterone concentrations in women with preterm labor 13 and preterm delivery. 3,6,9,11 Progesterone, estradiol, and estriol in relation to preterm delivery have mainly been investigated in singleton pregnancies 3,4,6,7,[9][10][11][12][13][14] and few results have been published from multiple pregnancies. 3,6,9,11 Progesterone, estradiol, and estriol in relation to preterm delivery have mainly been investigated in singleton pregnancies 3,4,6,7,[9][10][11][12][13][14] and few results have been published from multiple pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone is a key hormonal regulator of the female reproductive system and plays a major role in preparing the uterus for implantation and in the establishment and maintenance of pregnancy (32,33). PTB in women is associated with changes in circulating hormones such as progesterone deficits (34)(35)(36)(37)(38) or with inadequate responses to progesterone (32,39). To further demonstrate the effectiveness of bitter tastants in preventing PTB, we established another mouse model of preterm labor with the progesterone receptor antagonist RU-486.…”
Section: Bitter Tastant Chq Protects Against Mouse Ptbs Better Than Cmentioning
confidence: 99%
“…Three later studies, two in saliva and one on serum, suggested that repeating measurements of hormones to generate a “hormone profile” may be more useful than a single measure [810]. Priya et al .…”
Section: Introductionmentioning
confidence: 99%
“…and Lachelin et al . found that low saliva P4 between 24–34 weeks was associated with spontaneous PTB before 34 weeks [8,9]. Smith et al .…”
Section: Introductionmentioning
confidence: 99%